Two new Smith predictor proposals for performance and robustness enhancement for systems with elevated time delay - Martínez, Jesús; Camacho, Oscar (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This paper presents two new strategies, based on the Smith predictor, to control self-regulating systems with elevated deadtime. The first one uses two modifications done in previous works, one accelerates the regulatory response and the other improves the robustness maintaining a simple tuning, while the second one consists on the use of the sliding mode control to improve the system's robustness